The Garos : struggling to survive in the valley of death - Rahman, Mizanur, 1956-; Empowerment Through Law of the Common People (Project) (Dhaka : Empowerment through Law of the Common People, 2006)
Contributed articles with reference to Bangladesh.
"CLR publication, ELCOP."
Includes bibliographical references (p. 291-301).
Keywords: Garo (Indic people) -- Bangladesh -- History; Garo (Indic people) -- Bangladesh -- Social conditions